Performance Determinants - Irfan Siregar, Zulkhaidir; B, Mesra (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
In fact, HR sets the standards for managing a business. Various factors contribute to the prosperity of institutions, organizations, and businesses. However, the human element holds the key to success in achieving this goal. Even if other resources are available, a business will find it difficult to function well without quality human resources. Human resources are one of the most important factors in a company. The results of this research are as follows: Emotional Intelligence has a positive and significant effect on Employee Performance with a value of 0.332 and a value of 0.009. Emotional Intelligence has a positive and insignificant effect on Organizational Citizenship Behavior with a value of 0.200 and a value of 0.023. Organizational Citizenship Behavior has a positive and significant effect on Employee Performance with a value of 0.168 and a value of 0.162. Training has a positive and significant effect on employee performance with a value of 0.356 and a value of 0.016. Training has a positive and significant effect on Organizational Citizenship Behavior with a value of 0.710 and a value of 0.000. Emotional Intelligence has a positive and insignificant effect on Employee Performance through Organizational Citizenship Behavior with a value of 0.034 and a value of 0.204. Training has a positive and insignificant effect on Employee Performance through Organizational Citizenship Behavior with a value of 0.119 and a value of 0.169.